Adoption of chilli Production Technology Among the chilli Growers in Sehore District of Madhya Pradesh - Abhilasha Sharma , Mukesh singh , S. N. Sharma and S. B. Tambe, (Indian Journal of Extension Education, 2015)
This study was conducted in Sehore district of Madhya Pradesh in the year of 2013-14. The study revealed that majorityof the chilli growers had high adoption behaviour (46.08%) followed by medium level of adoption(36.42%) and lowadoption behavior ( 17.50%) regarding overall recommended chilli production technology respectively. The study alsorevealed that the socio-economic factors had positive and significant influence on the adoption of chilli productiontechnology, among the chilli growers .